Kinetic study of bioactive compound extraction from cacao shell waste by conventional and deep eutectic solvent - Irsal, Muh.; Kusumastuti, Yuni; Ariyanto, Teguh; Putri, Nur Rofiqoh Eviana (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2025)
Cacao shells contain bioactive compounds such as phenolic acids and flavonoids. This study investigated the potential of bioactive compound extraction in cacao shells using conventional and green solvents like deep eutectic solvent (DES) (choline chloride: lactic acid). Specifically, it investigated the extraction kinetic models and parameters, which are critical to scale up the extraction process. The extraction of cacao shell was conducted using various conventional solvents (ethanol, methanol, n-hexane, and water) and DES (100 % and 70%) in which the result showed that DES 100% had the highest total phenolic content of 337.92?±?9.55 mg GAE/g dry weight. Meanwhile, pseudo-second order and Peleg’s model provided the best fit for the experimental data with higher R2 values. DES 70% showed a higher total flavonoid content of 76.51?±?1.59 mg RE/g dry weight. FT-IR and Raman spectroscopy confirmed the presence of bioactive compounds in DES-based extracts, which revealed characteristic vibrational bands associated with polyphenolic structures. These include bands corresponding to hydroxyl (–OH), carbonyl (C=O), and aromatic C=C stretching—functional groups commonly found in quercetin and other bioactive compounds.